Spectrum - simulador de eventos discretos em redes ópticas elásticas, aplicado a uma interface gráfica - Regis, Gabriel Biesek (2020)
The Elastic Optical Networks (EONS) have brought great advances in the computer networks area, while providing high amounts of bandwidth. Hence, connections with high transmission rate became possible. Therefore, the elastic optical networks arrived to save the spectrum resources by making them flexible. In order to validate the computer networks behaviors while experimenting and developing new scientific approaches to increase its efficiency, discrete-event simulations are commonly used. However, one the major problems with optical networks simulation is the educational and user experience worry-free simulators available. This work proposes an Elastic Optical Network simulator, developed through a graphic interface and an interactive help system. Lastly, the developed simulator will be evaluated by the Communicability Evaluation Method (CEM).